Mutations in the Human UBR1 Gene and the Associated Phenotypic Spectrum. Issue 5 (9th April 2014) - Sukalo, Maja; Fiedler, Ariane; Guzmán, Celina; Spranger, Stephanie; Addor, Marie‐Claude; Mcheik, Jiad N.; Oltra Benavent, Manuel; Cobben, Jan M.; Gillis, Lynette A.; Shealy, Amy G.; Deshpande, Charu; Bozorgmehr, Bita; et al.
<x xml:space="preserve">Abstract</x> This article reviews 60 UBR1 mutations including 31 novel ones observed in 50 families affected by Johanson–Blizzard syndrome. Genotype‐phenotype correlations are reported. Additionally, diagnostic criteria for the syndrome are proposed on the basis of the clinical data collected from individuals with a molecularly confirmed diagnosis of Johanson–Blizzard syndrome. A database was set up at LOVD, providing public access to genotype and phenotype data. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>